Perancangan Front-End Aplikasi Lapis Satu Berbasis Flutter pada Badan Pusat Statistik Kabupaten Madiun - Dany Setiyawan; Farel Bernard Ganendra; Andria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to design and implement the user interface of the Lapis Satu (Integrated Complaint and Statistical Dissemination Service) application using Flutter at the Central Bureau of Statistics (BPS) of Madiun Regency. The application was developed to integrate multiple public services, including complaints, data requests, consultations, internships, and infographic galleries, into a single digital platform. The development process adopted the Agile Development methodology, consisting of three main stages: Planning, Design, and Development. The design phase utilized Figma to create an interface aligned with BPS’s visual identity, while the implementation phase used Flutter to build an interactive front-end prototype. The results indicate that applying the Agile approach is effective for iterative and flexible system development. The prototype successfully presents all major public service features and runs stably on an Android emulator. Therefore, this project provides a foundational framework for further development, including backend integration and full system deployment within BPS Madiun Regency.